The amphibian community at Yanayacu Biological Station, Ecuador, with a comparison of vertical microhabitat use among Pristimantis species and the description of a new species of the Pristimantis myersi group - Guayasamin, Juan M.; Funk, W. Chris (Zootaxa, 2009)
We provide information regarding the composition of the amphibian community at Yanayacu Biological Station, on the Amazonian slopes of the Andes of Ecuador, and describe a new species of Pristimantis that is referred to the P. myersi group. The new species is distinguished from other species of the group mainly by its color pattern, and by lacking ulnar and tarsal tubercles. The advertisement call of the new species has two distinct call types, a short call with 1–3 pulses and a long call with a mean of 15.5–18.9 more rapid pulses, which are often produced together in long call series. Finally, we analyze the microhabitat use of Pristimantis species found at Yanayacu and find that there is significant variation in vertical habitat use among Pristimantis, highlighting the ecological diversity of sympatric species.